2019
DOI: 10.1590/2175-8239-jbn-2018-0122
|View full text |Cite
|
Sign up to set email alerts
|

Thumb adductor muscle thickness used in the nutritional assessment of chronic kidney disease patients under conservative treatment

Abstract: Introduction: Evaluate the association between the thumb adductor muscle thickness and the patient's nutritional status, and propose cutoff points for muscle mass depletion in elderly patients with chronic kidney disease (CKD) under conservative treatment. Epidemiological and cross-sectional study, including patients with CKD stages 3 to 5, older than 60 years. Socioeconomic, clinical, physical activity and anthropometric data was obtained. TAMT was described and compared according to CKD stage, socioeconomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
1
0
2
Order By: Relevance
“…Research to date has focussed on the effect of physical activity and exercise interventions on muscle mass, muscle strength and physical capacity. Relating to muscle mass, to date of the 14 studies which sought to investigate the effect of differing exercise interventions, 6 reported a positive effect on muscle mass [ 24 26 ] or muscle volume [ 27 ] with a mix of high and low risk of bias, with 10 of these studies being RCTs in design. Of the RCTs, 8 studies contained an aerobic training element with 38% (3/8 studies) reporting beneficial effects of aerobic training on muscle mass or a surrogate marker of muscle mass (ie.…”
Section: Non-dialysis Ckd (Stages 1–5)mentioning
confidence: 99%
“…Research to date has focussed on the effect of physical activity and exercise interventions on muscle mass, muscle strength and physical capacity. Relating to muscle mass, to date of the 14 studies which sought to investigate the effect of differing exercise interventions, 6 reported a positive effect on muscle mass [ 24 26 ] or muscle volume [ 27 ] with a mix of high and low risk of bias, with 10 of these studies being RCTs in design. Of the RCTs, 8 studies contained an aerobic training element with 38% (3/8 studies) reporting beneficial effects of aerobic training on muscle mass or a surrogate marker of muscle mass (ie.…”
Section: Non-dialysis Ckd (Stages 1–5)mentioning
confidence: 99%
“…Pereira P y colaboradores (37) realizaron un estudio cuyo objetivo fue evaluar la asociación del grosor del músculo aductor del pulgar (TAMT) con el estado nutricional y proponer puntos de corte para la evaluación de la depleción de masa muscular en pacientes ancianos con ERC en tratamiento conservador. El TAMT se midió con el individuo sentado, con las manos relajadas y sobre las rodillas, y los brazos apoyados en los muslos, con el codo en flexión de 90° aproximadamente.…”
Section: Evaluación Antropométricaunclassified
“…Pereira P y colaboradores (37) En todos los pacientes se evaluaron medidas antropométricas como TAMT, IMC, CP, CMBM y PCT; para la evaluación de la composición corporal se utilizó bioimpedancia tetrapolar. Se calculo TFG.…”
Section: Hallazgosunclassified